Weed Management of Kenaf (Hibiscus Cannabinus) Through Intercropping Leafy Vegetables And Cultural Practices (SAARC Journal of Agriculture, 2021)
A field experiment was conducted at Jute Research Experimental Station, Manikganj, Bangladesh during 2017 and 2018 cropping seasons to study the feasibility of intercropping leafy vegetables at early stage of the fibre crop: kenaf along with conventional weeding methods for better weed suppression and higher productivity. A Randomized Complete Block Design (RCBD) was followed consisting of eight treatments with three replications. Three leafy vegetables: red amaranth, jute shak and kangkong were used as intercrop with kenaf following 1 hand weeding and 1 hand hoeing alternately. Sole kenaf (weeded twice) was also grown as control. The total weed vegetation was comprised of grasses 49%, broadleaved 33% and sedge only 18%. Performance of kangkong as intercrop was found better in terms of weed suppression. Hand weeding was found more efficient as a cultural weeding method in reducing weed density. Although intercropping resulted in significant yield reduction of kenaf but increased net return and benefit-cost ratio (BCR) by increasing kenaf equivalent yield (KEY). The land equivalent ratio (LER) was found higher in all intercropping treatments than sole kenaf which indicated more efficient utilization of land under intercropping. Red amaranth intercropping+1 hand weeding resulted the maximum gross return (TK.1,36,200 ha-1) while the highest gross margin (Tk. 59,390 ha-1) and BCR (1.78) was obtained from jute shak intercropping+1 hoeing. Considering the production cost, monetary return and productivity, Kenaf intercropped with Jute shak+1 hoeing was found better than other intercropping treatments.SAARC J. Agric., 19(1): 165-176 (2021)